MALARIA INFECTION: SPECIATION, PARASITE DENSITY, ABO BLOOD GROUP, AND HAEMOGLOBIN CONCENTRATION AMONGST THE INHABITANTS OF BILLIRI LOCAL GOVERNMENT AREA, GOMBE STATE - Ishaku, Nassai; Chessed, G.; Pukuma, M. S.; Na’acha, F. E.; Kure, N. H. (FUDMA JOURNAL OF SCIENCES, 2021)
The study determines malaria infection with relation to sociodemographic characteristics, parasite density, plasmodium species, ABO blood group, anaemia, and haemoglobin concentration of the participants in Billiri LGA, Gombe State. Informed consent was obtained, and a template was designed containing sociodemographic characteristics of the participants. 381 blood samples were collected and examined using thin and thick film. Out of which 148(38.8%) were infected. Female had the highest infection 82(55.4%) compared to their male counterparts 66(44.6%), with regards to age, those within the age group 11-15years had the maximum infection 41(27.7%) and the least were those within 0 – 5years 3(2.0%). The employment status revealed; others which include students, housewife, and applicants had 49(33.1%) malaria which is the maximum and the minimum was the public servants 25(16.9%), marital status also showed that singles had the highest prevalence 74(50.0%) and the lowest was the widows 8(5.4%), there was a highly significant difference in the sociodemographic characteristics of the participants, p>0.05. With regards to parasitological indices; ABO blood group depicts, participants with blood group O had the maximum infection 60(40.5%) and the least are those with AB 22(14.9), the predominant Plasmodium species is P. falciparum 148(100%), those with moderate parasite density had the highest infection rate 75(50.7%), and 24(16.2%) from those with high, while haemoglobin concentration shows those that are not anaemic had 38(25.7%) infection, and those with critical were 19(12.8%), p<0.05 in all the parasitological indices which is insignificant statistically. Based on this findings, malaria infection is moderate in the study area